Dengue surge in Pakistan amidst the torrential rains: The threat of a potential outbreak. Issue 1 (30th November 2022) - Shoaib, Aqsa; Salim, Najwa; Waseem, Summaiyya
Abstract: With 390 million infections occurring globally and the infection putting half of the world's population at risk, dengue is an illness with potential, life‐threatening manifestations such as plasma leakage and fluid retention, severe bleeding, and organ impairment. This disease is already lurking in the various regions of Pakistan, which was recently ravaged by decades' worst flood. With mosquitoes being its eminent transmission source, it is coherent that a country with massive flooding, accumulation of stagnant water, and lack of adequate drainage systems can lead to a dengue outbreak. Pakistan, a low‐middle‐income country, is still recuperating from the aftershocks of the pandemic, a recent cholera outbreak, and the massive economic destruction they caused, especially in the healthcare sector. Concerningly, the World Health Organization has already issued a "second catastrophe" warning for Pakistan in the aftermath of the fatal floods which have caused the destruction of hundreds of health facilities while physicians and medical workers on the ground scramble to combat outbreaks of waterborne and other illnesses. If the spread of dengue isn't contained immediately, it will destroy the healthcare systems across the country and result in massive fatalities. To avoid tragic consequences, the government and concerned authorities must devise plans to launch public health programs aimed at boosting knowledge of the disease, its symptoms, transmission, prevention, and control. In this commentary, we discuss the current spike of dengue virus, epidemiology, transmission patterns, and preventative efforts in the aftermath of Pakistan's disastrous floods.